Establishing highly-efficient surface faradaic reaction in flower-like NiCo2O4 nano-/micro-structures for next-generation supercapacitors. (1st June 2019) - Wang, Zixing; Su, Hai; Liu, Fangyan; Chu, Xiang; Yan, Cheng; Gu, Bingni; Huang, Haichao; Yang, Tao; Chen, Ningjun; Han, Yu; Deng, Weili; Zhang, Haitao; et al.
Abstract: As in the case of supercapacitors, spinel NiCo2 O4 shows the main drawbacks of objectionable pseudocapacitive mechanism, low-voltage polarization effect and confined ion-reaction dynamics, which result in constrained development, narrow work voltage, and low loading mass. Herein we combined two strategies to address these issues. The first one is to design the flower-like NiCo2 O4 through Ostwald ripening of ultrathin Ni-Co layered double-hydroxide petals. And the second one is to balance the asymmetrical capacitance for further promoting capacitive behavior. With rationally designing the nano-/micro-structures, flower-like NiCo2 O4 shows highly porous ultrathin petals interconnected with each other and massive interspaces between the petals. This unique microstructure endows flower-like NiCo2 O4 with rapid electrolyte ions diffusion and mass transfer reaction. Consequently, the flower-like NiCo2 O4 electrodes exhibit a high capacity of ∼350 C g −1 even the loading mass of up to 9 mg cm −2 . More importantly, the hybrid supercapacitors, assembled with flower-like NiCo2 O4 as cathode, deliver a high specific capacity of ∼85 F g −1 with capacitive ratio up to 74.3%, and a high working voltage of 1.55 V. The transformation of conventional battery-like materials into novel capacitive dominated materials through nano/micro-structural design and balance of asymmetrical capacitance is helpful to further understand the pseudocapacitive mechanism of transition metal oxides/sulfides and therefore will promote their practical application in next-generation of hybrid supercapacitors.